STRUKTUR TARI SAKIN DI NAGARI PITALAH KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Lativa Andriani; Afifah Asriati; Herlinda Mansyur (FBS Universitas Negeri Padang, 2016)
Abstract This article aims to analyze and describe the structures Sakin Dance in nagari Pitalah Kecamatan Batipuh Kabupaten Tanah Datar. The formulation of the problem What is the Structure Sakin Dance in nagari Pitalah Kecamatan Batipuh Kabupaten Tanah Datar. The research is a qualitative descriptive method of analysis. The object of this study was Sakin dance in Nagari Pitalah Batipuh District of Tanah Datar. Data was collected through literature study, work studio, observations, interviews, and documentation. While the research instrument that researchers themselves and use tools to record and collect data that use tools - stationery, photo camera, Handy-cam, tape recorder or hp. Data analysis was carried out based on the steps-steps proposed by Sugiono, namely data collection, data reduction, data presentation, and conclusion.The results showed that the hierarchical relationship management grammatical Sakin dance is composed of several constituent components, ranging from the smallest to largest component. The smallest component unit at the start of the kinetic elements, form a motif, then forming parts and eventually into motion a whole dance. Tata hierarchical relationships contained in Sakin dance consists of 109 overall kinetic and kinetic 25 primary, 29 motif, 6 parts and eventually become the overall dance movement called Sakin dance.Keywords: Structures, Motion, Sakin Dance.